THE USAGE OF MULTIPLE CHOICE AND GAP FILLING IN MEASURING GRADE-SCHOOLERS’ UNDERSTANDING OF GRAMMAR - Astri Yuniar Sri Utari (STKIP Siliwangi, 2013)
Grammar is one of the important elements in English that must be mastered or at least understood by the learners. In measuring students’ understanding of grammar, teachers can use four kinds of tests. They are gap filling, paraphrase, completion, and multiple choice. Multiple choice and gap filling are commonly used in assessing grade-schoolers’ understanding of grammar. Both of them are considered easy tests. Thus, there shouldt be no difference in students’ scores, whether using multiple choice test or gap filling test. This study is conducted to find a brief comparison of the usage of multiple choice and gap filling in measuring their understanding of grammar. This study also tries to determine which test is more influential in measuring the students’ understanding of grammar. This study uses quantitative approach. The data collection is obtained from students’ scores in both tests and the questionnaires. Through data analysis it is found that there is a significant difference in students’ scores of multiple choice and gap filling test. Students’ multiple choice scores are significantly better than their gap filling scores. It is also found that most of students believe that gap filling test is better than multiple choice test to assess their understanding of grammar. KEYWORDS: grammar, multiple choice test, gap filling test, paraphrase, completion